THE IMAGE OF INDIA IN 19TH-CENTURY SLOVAK LITERATURE - Gáfrik, Róbert (Porównania, 2018)
The European Oriental Renaissance began with the discovery of Sanskrit which gave birth to comparative philology, the pre-eminent academic discipline of the 19th century. The Czech philologist Josef Dobrovský (1753–1829) and the Polish scholar of Sanskrit Walenty Skorochód Majewski (1764–1835) very soon discovered similarities between Indian and Slavic languages and consequently many Slavic scholars began to see India as the Slavic homeland. The great Slovak Romantic poets such as Ján Hollý (1785–1849) and Ján Kollár (1793–1852) considered India to be the homeland of the Slavs, as did Ľudovít Štúr (1812–1856), the main leader of the Slovak national revival in the 19th century, although, as a Hegelian, he was critical of Indian religion and of the caste system. The paper reconstructs the image of India in Slovak literature of the 19th century which ranges from a fascination with the idea of the Slavic homeland in India in the first half of the 19th century to its refusal in the light of the theory of Aryan invasion in the second half of the 19th century. It focuses on the changing image of the Indian Other and on the self-image of the Slavs vis-à-vis India.